1998
DOI: 10.1074/jbc.273.39.25006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Conserved α-Helix in the Kinase-docking Region of the Aspartate Receptor by Cysteine and Disulfide Scanning

Abstract: The transmembrane aspartate receptor of Escherichia coli and Salmonella typhimurium propagates extracellular signals to the cytoplasm, where its cytoplasmic domain regulates the histidine kinase, CheA. Different signaling states of the cytoplasmic domain modulate the kinase autophosphorylation rate over at least a 100-fold range. Biochemical and genetic studies have implicated a specific region of the cytoplasmic domain, termed the signaling subdomain, as the region that transmits regulation from the receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
139
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(146 citation statements)
references
References 69 publications
6
139
1
Order By: Relevance
“…This probe reacts quickly with solvent-exposed sulfhydryls, but it is largely excluded from the interior of a protein and therefore reacts slowly with buried sulfhydryls. Previous experiments have experimentally confirmed the accuracy of this approach using helix α2, a helix of known structure in the receptor periplasmic domain, as a control (63). This previous analysis scanned a single cysteine from positions T95-H103 on helix α2 in the full-length, membrane-bound receptor and measured the chemical reactivities of each position with three different probes, including 5-IAF.…”
Section: Chemical Reactivity Analysis Of Solvent Exposure and Secondamentioning
confidence: 92%
“…This probe reacts quickly with solvent-exposed sulfhydryls, but it is largely excluded from the interior of a protein and therefore reacts slowly with buried sulfhydryls. Previous experiments have experimentally confirmed the accuracy of this approach using helix α2, a helix of known structure in the receptor periplasmic domain, as a control (63). This previous analysis scanned a single cysteine from positions T95-H103 on helix α2 in the full-length, membrane-bound receptor and measured the chemical reactivities of each position with three different probes, including 5-IAF.…”
Section: Chemical Reactivity Analysis Of Solvent Exposure and Secondamentioning
confidence: 92%
“…Cysteine scanning and solvent exposure studies have probed the secondary structure of the cytoplasmic domain and have identified six regions of α helix, some of which could represent different sections of a longer continuous helix ( [43][44][45]46••]; also S Winston, JJ Falke, unpublished data). These chemical studies analyzed a representative family A chemoreceptor, the S. typhimurium aspartate receptor, in its full-length, membrane-bound state.…”
Section: Conserved Cytoplasmic Domain Of the Methyl-accepting Taxis Pmentioning
confidence: 99%
“…The chemical analysis of the cytoplasmic domain architecture, carried out in the intact, membrane-bound aspartate receptor [2••], began with the prior knowledge of large helical regions defined by the aforementioned cysteine scanning and solvent exposure studies ( [43][44][45]46••]; also S Winston, JJ Falke, unpublished data). The packing of these helical regions was elucidated by measuring disulfide bond formation rates between a set of 44 cysteine pairs engineered at buried positions to test for specific helix-helix contacts within and between different subunits [2••].…”
Section: The Cytoplasmic Domain Is a Dimeric Extended Four-helix Bumentioning
confidence: 99%
“…Covalent neutralization of an interfacial anion by methyl esterification or amidation stabilizes the interface and activates kinase, whereas simultaneous neutralization of all anions locks the receptor in the kinaseactivating state [58] Conformational signaling in the protein interaction region, where the kinase interacts, remains poorly understood. However, like the adaptation region, its subunit interface seems to be crucial for signal transmission because many 'lock-on' mutations occur at interfacial locations [54,59]. …”
mentioning
confidence: 99%